Emergence phenology of the giant salmonfly and responses by birds in Idaho river networks - Adams, McKenna M.; Baxter, Colden V.; Delehanty, David J. (Frontiers in Ecology and Evolution, 2023)
Emergence of adult aquatic insects from rivers is strongly influenced by water temperature, and emergence timing helps to determine the availability of this ephemeral food resource for birds and other terrestrial insectivores. It is poorly understood how spatial heterogeneity in riverine habitat mediates the timing of emergence. Such spatiotemporal variation may have consequences for terrestrial insectivores that rely on aquatic-derived prey resources. We investigated emergence phenology of the giant salmonfly, Pteronarcys californica, at three spatial scales in two Idaho river networks. We examined the influence of tributary confluences on salmonfly emergence timing and associated insectivorous bird responses. Salmonfly emergence timing was highly variable at the basin-scale during the period we sampled (May-June). Within sub-drainage pathways not punctuated by major tributaries, emergence followed a downstream-to-upstream pattern. At the scale of reaches, abrupt changes in thermal regimes created by 10 major tributary confluences created asynchrony in emergence of 1-6 days among the 20 reaches bracketing the confluences. We observed 10 bird species capturing emerged salmonflies, including 5 species typically associated with upland habitats (e.g., American robin, red-tailed hawk, American kestrel) but likely aggregated along rivers to take advantage of emerging salmonflies. Some birds (e.g., Lewis’s woodpecker, western tanager, American dipper) captured large numbers of salmonflies, and some of these fed salmonflies to nestlings. Emergence asynchrony created by tributaries was associated with shifts in bird abundance and richness which both nearly doubled, on average, during salmonfly emergence. Thermal heterogeneity in river networks created asynchrony in aquatic insect phenology which prolonged the availability of this pulsed prey resource for insectivorous birds during key breeding times. Such interactions between spatial and temporal heterogeneity and organism phenology may be critical to understanding the consequences of fluxes of resources that link water and land. Shifts in phenology or curtailment of life history diversity in organisms like salmonflies may have implications for these organisms, but could also contribute to mismatches or constrain availability of pulsed resources to dependent consumers. These could be unforeseen consequences, for both aquatic and terrestrial organisms, of human-driven alteration and homogenization of riverscapes.